Reinforced concrete structural elements cast into wood-chip cement formworks subjected to compression and out-of-plane bending. (1st November 2021) - Scotta, Roberto; Trutalli, Davide
Highlights: RC walls cast into permanent woodchip-cement formworks are analysed. The mechanical response of the wall subjected to eccentric compression is discussed. Tests of panels with varying reinforcement, section and eccentricity are presented. An analytical model to evaluate the load-bearing capacity is proposed. The analytical model for verification of masonry is extended to RC grid panels. Abstract: The mechanical response of reinforced concrete walls cast into permanent woodchip-cement formworks and subjected to eccentric compression has been assessed with experimental tests of full-scale panels and an analytical approach has been proposed. The load-bearing capacity of the wall panel is assured by the inner reinforced concrete grid structure, composed of vertical columns and horizontal ribs, reinforced with vertical and horizontal steel bars. The experimental specimens were realized varying the concrete cross-section and tested varying the eccentricity of the applied vertical load. Both reinforced and non-reinforced panels were tested. An analytical model is proposed to evaluate the load-bearing capacity, based on dimensionless curves, which provide reduction coefficients of strength based on eccentricity and slenderness, considering second-order effects. The analytical model demonstrates a reliable prediction of the experimental peak loads.